Viewing Boykin and Schoenhofer’s Nursing as Caring Through Parse’s Criteria for Evaluation of Theorie - Lacdo-o, Maybelle R. (Silliman Journal, 2022)
Brown (1997) emphasized that one of the recent trends in the nursing profession in most, if not all, cultures is to produce, utilize, and practice research-based nursing care. Inherent in this goal is the continued development and testing of nursing theory. In order to utilize nursing theory appropriately it is important to know how to describe, analyze, and critique (evaluate) theory. While empirical testing of theory is important, it is but one part of the evaluation of theory. Meleis (1985) states that theory evaluation provides for constructive criticism, further theory development, and helps the evaluator develop an appreciation for the process of theory development. Essentially, one main purpose of evaluation is to allow for an informed critique of theory before (and after) conducting research, and before the application of a theory in practice or educational settings. While evaluation of theory is a combination of both subjective and objective findings, it is the premise of this paper that this objectivity can be accomplished through the use of criteria for evaluation that are acceptable to the profession yet culturally and geographically transferable. Kuhn(1977) once said that “we can delineate such criteria and that accuracy, consistency, broad scope, simplicity and fruitfulness in research are essential as objective criteria for judging competing theories.” We should always consider that every person’s between competing theories depends on a combination of empirical and subjective factors.” The subjective factors are dependent on the evaluator’s preferences, personalities and experiences. But it is indeed undeniable that Both objective and subjective factors have a place in our understanding of the philosophy of science. While many contemporary authors and theorists in nursing claim that we do not really utilize proposed nursing theories and conceptual models, they should be evaluated. Proper evaluation can lead to informed use and testing of nursing theory. From evaluation, will emerge criteria to improve upon the ideas already proposed, as well as provide a common denominator for further theory Development. In the literature there are many criteria proposed for the evaluation of theory. There are criteria proposed by philosophers of science (Kuhn, 1977; Newton-Smith, 1981; Laudan, 1977) as well as nursing theorists.